Carbon Trading Potential in the Forest Sector: Analysis at the Province Level in Indonesia - Kartiasih, Fitri; Azhari, Azhari; Rinangku, Rahadian Eka Bagus Indra (Eko-Regional: Jurnal Pembangunan Ekonomi Wilayah, 2025)
Forests are ecosystems that provide various important services for humanity, especially in mitigating climate change. Forests in Indonesia, as carbon absorbers and stores, have large market potential, where the carbon market provides opportunities to fund forestry sector projects. However, the forestry sector in Indonesia has not been able to take maximum advantage of the carbon market. This study aims to describe the condition and potential of the forestry sector carbon market, as well as estimate the carbon trading value of the forestry sector for 34 provinces in Indonesia in 2022. The method used is K-Medoids and calculating the carbon trading value. The study results show that areas on Papua Island and Kalimantan Island are the main potential contributors to carbon trading in Indonesia. These two islands have large areas of primary forest that are still maintained. This shows that the forest area in Papua Province is a strategic asset for Indonesia in its efforts to mitigate climate change through carbon trading.